Optimalisasi IPAL Prototipe Menggunakan Biofilter Sarang Tawon sebagai Media Degradasi Polutan Limbah Laundry - Alricha Alricha; Awwalini Maghfirah Salim; Moh Baitullah Amaludin; Anita Pratiwi; Ardini Wulandari; Fatimah Maulida; Istiqomah Shariati Zamani (Jurnal Teknologi Berkelanjutan, 2025)
Domestic wastewater treatment often faces challenges due to high concentrations of organic matter and dissolved solids that can pollute the environment if left untreated. This study aims to evaluate the performance of a honeycomb biofilter in reducing key wastewater pollutants. The method applied was a laboratory-scale experiment using a small-scale WWTP system equipped with a honeycomb biofilter unit. The treatment results showed a significant reduction of BOD from 56 mg/L to 4.15 mg/L (92% efficiency), COD from 224 mg/L to 5 mg/L (97% efficiency), and TDS from 290 mg/L to 194 mg/L (30% efficiency). All parameters meet the quality standards. However, pH decreased from 7.4 to 4.4 (40% reduction), indicating the need for a pH adjustment unit before final discharge. In conclusion, the honeycomb biofilter proved effective in reducing organic load and dissolved solids, although integration with a pH neutralization unit is required to comply with environmental standards.